FTC Versus Congress: The Biosimilars Debate - CARR, KATHLEEN (BioCommunications LLC, 2009)
A Federal Trade Commission report dismissed the need for a period of market exclusivity for brand-name biologics that may face follow-on competition. The authors argue that the FTC’s conclusion –that patent protection alone will fuel biotech R&D after passage of follow-on legislation – is shaky.